Effects of ionic liquid blending in polymeric membrane: Physical properties and performance evaluation - Mohshim, D.F. (Trans Tech Publications Ltd, 2014)
Polymeric membranes have been extensively used in membrane gas separation process. Nowadays, peoples are modifying the membrane by many ways like coating with ionic liquids to further enhance the membrane separation performance. In this project, ionic liquid modified polymeric membranes (ILMPM) have been successfully developed by blending the ionic liquids with the polymer via solvent evaporation method. The ionic liquid used was 1-ethyl-3- methylimidazolium bis(trifluoromethylsulfonyl)imide, (emimTf2N) and for comparison purpose, the compositions were varied at 10 and 20 wt/wt%. In general, the blending of emimTf2N and PES has produced dense membrane with miscible mixture without any phase separation. It was observed that, the CO2 permeance of ILMPM has been improved about 271% as compared to the pure PES membrane. However, the CO2 permeance decreased with increasing operating pressure, yet the ILMPM CO2 permeance still higher than CO2 permeance of pure PES membrane. In addition, the CO2/CH4 separation performance has greatly increased about 162% as the IL composition is increased. This initial study has proven that IL helps to enhance of CO2 permeation and improve selectivity. Â© 2014 Trans Tech Publications, Switzerland.